Sensorium R(A) : the Singapore International Film Festival (1987-2000) - Ng, Chrystal Shu Min (2017)
Introduced into Singapore’s cultural landscape in 1987, the Singapore International Film Festival (SIFF) has been providing a space for cine-philes in the region. Founded by Australian expatriate, Geoffrey Malone, SIFF was largely headed by film festival stalwarts, Philip Cheah and Teo Swee Leng. Known in the international film festival (IFF) circuit today as a key champion of Southeast Asian (SEA) cinema within the region. SIFF has been actively carving out this niche since its 1995 edition – one that still forms the core of the Festival today. Local filmmakers and film industry professionals have attributed their successes on the global IFF circuit to the exposure provided by the showcasing of their work at SIFF’s Silver Screen Awards.